Advances in Symbiotic Bioabsorbable Devices - Chang Zhu; Engui Wang; Zhou Li; Han Ouyang (Advanced Science)
Abstract Symbiotic bioabsorbable devices are ideal for temporary treatment. This eliminates the boundaries between the device and organism and develops a symbiotic relationship by degrading nutrients that directly enter the cells, tissues, and body to avoid the hazards of device retention. Symbiotic bioresorbable electronics show great promise for sensing, diagnostics, therapy, and rehabilitation, as underpinned by innovations in materials, devices, and systems. This review focuses on recent advances in bioabsorbable devices. Innovation is focused on the material, device, and system levels. Significant advances in biomedical applications are reviewed, including integrated diagnostics, tissue repair, cardiac pacing, and neurostimulation. In addition to the material, device, and system issues, the challenges and trends in symbiotic bioresorbable electronics are discussed.